2014
DOI: 10.1021/ma500282b
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Functionalized Polymers to Surface-Attached Polymer Networks Containing Reactive Groups

Abstract: To study diffusion and binding of polymers into surface-attached networks containing reactive groups, surface-attached polymer networks bound to oxidized silicon surfaces are generated, which contain succinimide ester groups. The surface-attached polymer layers are brought into contact with poly(ethylene glycol)s (PEG), which carry terminal amine end groups and which have systematically varied molecular weights. The coupling reaction between the active ester groups in the polymer networks and the amine groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…this was the temperature limit used for all the cases. While a higher density of the grafted polymer caused problems in getting stronger adhesion in other studies, [13][14][15] this was not observed in the current one. A possible reason could be the longer processing time used for the process.…”
Section: Adhesion Behavior Of Ti-pmma-ti Sandwichescontrasting
confidence: 69%
See 1 more Smart Citation
“…this was the temperature limit used for all the cases. While a higher density of the grafted polymer caused problems in getting stronger adhesion in other studies, [13][14][15] this was not observed in the current one. A possible reason could be the longer processing time used for the process.…”
Section: Adhesion Behavior Of Ti-pmma-ti Sandwichescontrasting
confidence: 69%
“…In previous studies, it was found that highly dense grafted polymers result in decreased adhesion, as it leads to overlapping of grafted chains, thus preventing interpenetration. [13][14][15] Thus, the grafted chain density should be in a regime where they can easily move and interpenetrate in the adhering polymer. As polymer autohesion is also a timedependent process, by increasing the processing time, the degree of bonding between the polymers will also increase.…”
Section: Introductionmentioning
confidence: 99%
“…To this first a copolymer containing photoactive benzophenon groups (PDMAA‐ co ‐MABP) is generated from N , N ′‐dimethylacrylamide (DMAA) and 4‐methacryloyloxybenzophenone (MABP). The synthesis of the polymers and the photocrosslinking for the generation of surface‐attached networks from these layers has been described in detail in previous publications . Briefly, upon irradiation of the dry, glassy polymer film with UV light the benzophenone units are excited into a biradicaloid triplet state, abstract a hydrogen from any alkyl moiety in the vicinity such as a neighboring polymer chain, followed by radical–radical coupling leading to a covalent linking of the chains (C,H insertion crosslinking, Chic).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that due to the stretching and the block‐like segment density profile exhibited by swollen surface‐attached networks such systems are strongly impermeable by other macromolecules, which strongly prevents any interpenetration by other chains coming in from the outside. This effect was found to be even more pronounced than that of polymer brushes as penetration occurs only at the outer periphery of the layers and surface‐attached networks can have an even steeper segment density profile compared to brushes . As the essential physics of surface‐attached gels is very different from that of free gels also the friction properties should be very different.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10,11 ] Numerous strategies have been developed for controlled interfacing of these polymer networks with solid substrates via specific interactions including on‐surface growth of polymer networks. [ 12,13 ] These avenues have been explored in supramolecular polymer systems to much lesser extent, primarily relying on poorly controlled and nonspecific interactions between supramolecular fibers. [ 14 ] Recently reported chemically cross‐linked supramolecular fibers yielding strain‐stiffening, self‐healing hydrogels demonstrate their potential as dynamic new materials.…”
Section: Introductionmentioning
confidence: 99%